Potensi Gua dan Ceruk di Kabupaten Aceh Tengah Bagi Pengembangan Penelitian Arkeologi dan Pariwisata - Nenggih Susilowati (Berkala Arkeologi Sangkhakala, 2008)
AbstractCave and rock shelter contain the natural and cultural resources for research and development sciences. The society and tourism sector have their own importance of that object. However, we should have pay particular attention to its conservation and perpetuation.